Exploring the outcomes of non-surgical periodontal therapy in modulating periodontal parameters, renal function, and inflammatory biomarkers in chronic kidney disease patients with periodontitis - Rajaratinam, Harishini; Abdul Rahman, Nurul Aliya; Hanafi, Muhammad Hafiz; Siti Lailatul Akmar Zainuddin, Siti Lailatul; Ibrahim, Hanim Afzan; Kamarudin, Muhammad Imran; Wan Zain, Wan Mohd Saifuhisam; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Isa, Salbiah; Kassim, Nur Karyatee (PeerJ Inc., 2025)
Background This comparative prospective cohort study investigated the outcomes of non-surgical periodontal therapy (NSPT) on periodontal parameters, renal function, and serum inflammatory markers in chronic kidney disease (CKD) patients with periodontitis. Methods Participants were categorised into three groups: CKD patients with periodontitis (CKD-P, n = 20), patients with periodontitis only (P, n = 20), and healthy participants (HP, n = 20). Periodontal parameters were initially evaluated for all participants. Blood samples were collected to assess renal function, including serum electrolytes, urea, creatinine and estimated glomerular filtration rate (eGFR), as well as inflammatory markers such as interleukin-6 (IL-6) and transforming growth factor-beta 1 (TGF-β1). NSPT was performed on both the CKD-P and P groups. Six weeks following treatment, periodontal parameters, renal function tests and inflammatory markers were re-evaluated to determine any modulation in these outcomes. Results The CKD-P group exhibited the highest concentration of potassium, urea, and creatinine. There were no significant differences in the periodontal pocket depth (PPD) and clinical attachment loss (CAL) means between CKD-P and P groups (P > 0.05). Similarly, there was no significant difference in the gingival bleeding index (GBI) scores between CKD-P, P, and HP groups (P > 0.05). However, the CKD-P group exhibited the highest plaque score (PS) compared to the P and HP groups (P < 0.0001). Post-NSPT, both the CKD-P and P groups showed significant improvement in these periodontal parameters. The median eGFR for the CKD-P group improved significantly (P < 0.0001) after NSPT. In terms of inflammatory markers, the IL-6 levels were significantly higher in the CKD-P group compared to the P and HP groups (P < 0.001). Additionally, there were significant differences in the TGF-β1 levels across all three groups (P < 0.05). Following post-NSPT, both CKD-P (P < 0.001) and P (P < 0.0001) groups demonstrated significant reductions in IL-6. As for the TGF-β1 level, significant reduction post-NSPT was only observed in the CKD-P group (P < 0.001). Conclusion NSPT is effective in enhancing periodontal health, improving renal function, and decreasing systemic inflammation in CKD patients with periodontitis